Epitope mapping of monoclonal antibodies: a comprehensive comparison of different technologies - Xibei Dang; Lars Guelen; David Lutje Hulsik; Grigori Ermakov; Edward J. Hsieh; Joost Kreijtz; Judith Stammen-Vogelzangs; Imke Lodewijks; Astrid Bertens; Arne Bramer; Marco Guadagnoli; Alexis Nazabal; et al. (mAbs, 2023)
ABSTRACTMonoclonal antibodies have become an important class of therapeutics in the last 30 years. Because the mechanism of action of therapeutic antibodies is intimately linked to their binding epitopes, identification of the epitope of an antibody to the antigen plays a central role during antibody drug development. The gold standard of epitope mapping, X-ray crystallography, requires a high degree of proficiency with no guarantee of success. Here, we evaluated six widely used alternative methods for epitope identification (peptide array, alanine scan, domain exchange, hydrogen-deuterium exchange, chemical cross-linking, and hydroxyl radical footprinting) in five antibody-antigen combinations (pembrolizumab+PD1, nivolumab+PD1, ipilimumab+CTLA4, tremelimumab+CTLA4, and MK-5890+CD27). The advantages and disadvantages of each technique are demonstrated by our data and practical advice on when and how to apply specific epitope mapping techniques during the drug development process is provided. Our results suggest chemical cross-linking most accurately identifies the epitope as defined by crystallography.